ILHAS DE CALOR EM CLIMA SUBTROPICAL ÚMIDO - Morsch, Maiara; Niemeyer, Lygia; Silvoso, Marcos; Spader, Júlia; Fengler, Jaqueline; Maziero, Bruna (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Cities characterized by humid subtropical climate have seen an increase in urban heat in recent years regardless of their size and density. In this sense, this research, which is in progress, is based on climate monitoring with dataloggers in four regions with distinct morphologies in a city with the mentioned climate. Temperature and humidity data are being collected every hour from August 20, 2017. In this way, the data of the winter, spring and summer seasons have been treated and the same are discussed in this work. The results demonstrate that, in addition to the constructive density, the way in which the buildings are inserted in the city, the infrastructure and the solar influence is determinant for the formation of the heat islands.